PERBANDINGAN ANGKA BEBAS BATU PADA PASIEN BATU KALIK DENGAN PEMBERIAN DIURESIS DAN TANPA DIURESIS SELAMA ESWL - Budiyono, Nur Budiyono; Soebadi, Doddy M; P, Widodo J (Indonesian Urological Association, 2009)
Objective: To compare effects of intravenous hydration, both with and without diuretics on the stone free rate of calyceal stones during ESWL. Materials and Methods: We analyzed 22 patients with calyceal stone, primarily treated with Sonolith Vision lithotripter, between June 2008 and October 2008. Patients were divided in 2 groups, the 11 patients in group 1 were injected with 500 ml normal saline for intravenous hydration, and 20 mg of furosemide for diuretic effect during ESWL; the 11 patients in group 2 were used as controls. The same energy settings for the shockwaves in one session were equally applied to all patients during ESWL, with a 1 Hz shockwave frequency, 100% power and 1000 shocks. After 2 weeks the stone free rate and residual fragments were evaluated on the post ESWL KUB and compared with the pre-ESWL KUB. Results: After a single ESWL treatment, the stone-free rate was 81,8% (9 of 11 patients) in group 1 and 63,3% (7 of 11 patients) in group 2. The stone free rates of group 1 was higher than that of group 2, but there was no statistical difference between groups 1 and 2. Conclusion: Intravenous hydration with normal saline with a furosemide injection for diuretic effect during ESWL would be same effective method to facilitate fragmentation and stone free of calyceal stones.